Effect of Heat Treatment on Microstructure Evolution and Mechanical Properties of 2.5 vol% TiBw/TA15 Composites with Different Deformation Statuses. Issue 10 (28th June 2018) - Jiao, Xueyan; Du, Dandan; Chen, Wenzhen; Zhang, Wencong; Yang, Jianlei; Cui, Guorong
Abstract : In this study, heat treatments of solution and aging are performed on 2.5 vol% TiBw/TA15 composites with different deformation statuses. The results indicate that the mechanical properties of the 2.5 vol% TiBw/TA15 composites are influenced by the microstructure, which is affected by the thermal processing and heat treatment history. The elongated α phase is obtained in the powder extrusion process followed by air cooling (EAC) and is then spheroidized in the rotary swaging process. After solution at 970 °C, the α phase is further spheroidized and partially transformed into the β phase at different degrees depending on the deformation status. After aging at 930 °C, the volume fraction of the equiaxial α phase increases significantly and the transformed β phase is decomposed into the clustered α + β laths at different degrees. Although experiencing the same post‐heat treatment, the influence of the deformation history affects the microstructure. After solution at 970 °C for 30 min and aging at 930 °C for 100 min, the EAC + RSAC sample exhibits an ultimate tensile strength of 1335 MPa and an elongation of 4.2%. Additionally, the fracture mechanism consists of the brittle fracture of the TiB whiskers and the ductile failure of the TA15 matrix. Abstract : This work investigates the heat treatment behavior with different deformation status of 2.5 vol% TiBw/Ti6Al4V composites. The results show that different deformation process obtain different microstructure and different cooling rate has a weak influence of the morphology of phases.